2009
DOI: 10.1029/2008jf001190
|View full text |Cite
|
Sign up to set email alerts
|

A model for the long‐profile shape of submarine canyons

Abstract: [1] Submarine canyons are shaped by turbidity currents flowing down the continental slope. But canyon morphology also depends on the patterns of sediment deposition that drive long-term outbuilding of continental margins. Relating the importance of each to the shape of canyon long profiles provides a tool for inferring process from observed (modern and buried) canyon morphologies. Here we present a morphodynamic model that predicts the equilibrium long-profile curvature of a canyon affected by turbidity curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 63 publications
1
62
0
Order By: Relevance
“…Concavity in the surface profile along the delta is expected. This has been demonstrated both in fluvially-formed landscapes [e.g., Sinha and Parker, 1996] and in the shape of submarine canyons [e.g., Gerber et al, 2009] under equilibrium steady-state conditions. Concavity in the surface profile is the result of the physically-based formulation of water and sediment fluxes in the model.…”
Section: Analysis Of Inland Delta Formationmentioning
confidence: 99%
“…Concavity in the surface profile along the delta is expected. This has been demonstrated both in fluvially-formed landscapes [e.g., Sinha and Parker, 1996] and in the shape of submarine canyons [e.g., Gerber et al, 2009] under equilibrium steady-state conditions. Concavity in the surface profile is the result of the physically-based formulation of water and sediment fluxes in the model.…”
Section: Analysis Of Inland Delta Formationmentioning
confidence: 99%
“…Many studies have dealt with quantitative analyses of digital elevation models, 95 particularly focusing on channel morphology, to obtain information on the character, 96 pattern and rates of tectonic deformation, and to develop long-term landscape evolution 97 models (e.g. Howard, 1994 from that of rivers because of the increase or loss of flow power with suspension or 144 deposition of particle load (Gerber et al, 2009). It has also been suggested that drainage 145 basin area in submarine canyons is not related to flow discharge as in terrestrial systems, 146 but results from the aggregation of random walks (Straub et al, 2007).…”
mentioning
confidence: 99%
“…In contrast, we think that long-profi le concavity in the modern canyon is a consequence of a shift in the relative importance of turbidity current sedimentation in the canyon. Long-profi le concavity is expected in submarine canyons and channels shaped by sediment transport in sustained, fully developed turbidity currents (Mitchell, 2005;Gerber et al, 2009;Spinewine et al, 2011), and will thus characterize equilibrium long profi les under conditions of sediment bypass or net deposition, the latter balancing subsidence and/or causing basinward progradation.…”
Section: Long-term Canyon Constructionmentioning
confidence: 99%
“…3B) similar to all Valencia Trough turbidite system modern canyons along the EM (Amblas et al, 2011). Following the model of Gerber et al (2009), we interpret this change in long-profi le curvature as a change in the relative importance of background sedimentation, construed here as a mix of hemipelagic settling and deposition from weak shelf gravity fl ows that dissipate below wave base (sensu Parker, 2006). The mid-Pleistocene (Pt2) canyon long profi le resembles the interfl uve long profi le, and its convex reach is located near the clinoform infl ection point that defi nes the midPleistocene shelf break.…”
Section: Long-term Canyon Constructionmentioning
confidence: 99%
See 1 more Smart Citation